Innovative Potential of the Regions in the Russian Arctic Zone: State and Spatial Differentiation - Sergey V. Tishkov; Nikolay E. Egorov; Aleksandr D. Volkov; Grigoriy S. Kovrov (Arctic and North, 2024)
The article considers the components of the innovation potential of Russian regions that are fully or partially included in the Arctic zone. The purpose of the article is to analyze and evaluate the state and dynamics of innovative development of the regions of the Arctic zone of the Russian Federation. The methodology for calculating the composite index of innovative development is proposed. The calculations are made on the basis of the database formed by the authors, which consists of four blocks; the main conclusions on the blocks are formed. According to the composite index for the period 20152021, the leading positions are occupied by the Krasnoyarsk Krai, the Arkhangelsk Oblast and the Komi Republic, and the Republics of Karelia, Sakha (Yakutia) and Komi in terms of the index growth rate. The study of the state, dynamics and level of innovation development in the regions of the AZRF shows that some components of innovation potential are unevenly developed in the regions that are fully or partially included in the AZRF. At the same time, the regions differ in the dynamics of innovative development. Thus, the worst indicators of innovative development in accordance with the proposed methodology are observed in the Arkhangelsk Oblast, Chukotka and Nenets Autonomous okrugs. The high correlation between the composite index of innovative development and indicators of socio-economic development of the regions revealed by the authors characterizes the positive impact of innovation activity on the socio-economic development of the AZRF subjects. In this regard, the key recommendations are the following: improvement of legislative support for the formation of eco-industrial, tourist zones, innovation sites and cluster formations in the Arctic territory within the framework of testing new formats of economic intensification of the Russian Arctic regions; formation of a macro-regional register of suppliers of innovative products for the projects of residents of the AZRF with the distribution of preferential measures ...